A review of literature on IFRS in Africa. Issue 1 (18th November 2019) - Tawiah, Vincent; Boolaky, Pran
Abstract : Purpose: This paper is an appraisal of existing literature on IFRS in Africa. In a bid to determine what exists and what is missing in the literature, the authors have reviewed three streams of studies, namely, adoption, compliance/harmonisation and consequences of IFRS in Africa, with the aim to suggest what remains to be investigated on IFRS in Africa. Design/methodology/approach: This paper uses a systematic review approach including synthesis of a variety of archival materials. Articles on Africa were summarised under three main headings: adoption, compliance/harmonisation and consequences of IFRS. Findings: This review finds limited research on IFRS in Africa. It reveals that although past cross-continent studies claimed to cover Africa, they are limited to only a few countries and mainly predominated by South Africa. The authors identified only one study that investigated the impact of economic and cultural factors on IFRS adoption in Africa and few cross-continent studies but considering only very few African countries. Regarding compliance, four studies concluded that compliance with IFRS is dependent on a firm's characteristics. The authors also identified that some of the generalised findings from prior research on consequences of IFRS are of limited significance in the African context. Originality/value: This study suggests the determinants of adoption, compliance and consequences of IFRS in Africa are different if studied separately. It identifies some gaps in the literature that require further research, specifically, IFRS on taxation, fair valuation practices and the institutional capacities of countries to implement the standards.